NP-013 Implementing the european statements of hospital pharmacy in italy: results of a working group. (March 2019) - Elizabeth Campbell Davies, Sophia; Ernestina Faggiano, Maria; Polidori, Carlo; Mancini, Mauro; Serra, Paolo; Zanon, Davide; Di Giorgio, Concetta; Bartolini, Fausto; Marinozzi, Andrea; Moretti, Vincenzo; Bianchi, Stefano; Pisterna, Alessia; et al.
Abstract : Background: The European Statements of Hospital Pharmacy express commonly agreed objectives which every European health system should aim for in the delivery of hospital pharmacy services to improve clinical outcomes and patient safety; 44 Statements are divided into six sections: (S1: Introductory Statements and Governance; S2: Selection, Procurement and Distribution; S3: Production and Compounding; S4: Clinical Pharmacy Services; S5: Patient Safety and Quality Assurance; S6: Education and Research). To obtain full achievement of the European Statements of Hospital Pharmacy, the European Association of Hospital Pharmacists (EAHP) has developed a project to implement the Statements within its member countries. The self-assessment tool (SAT), which allows hospital pharmacists to assess the level of implementation of the Statements within their hospitals, provides the means for hospital pharmacists to address the areas needing improvement with a tailor-made action plan and evidence-based resources, and to show progress over time, as it can be updated any time. The tool also helps hospital pharmacists to assess their status within their own countries and compare this to others. In order to implement the project in Italy, a working group was formed including Italian Society of Hospital Pharmacists (SIFO) representatives: the EAHP Delegate, the EAHP Ambassador, university professors, hospital pharmacists and local healthcare unit pharmacists from all over Italy (SIFO-EAHP-WG). Purpose: The objective of the work was to analyse the level of implementation of the Statements within the SIFO-EAHP-WG healthcare services. Materials and methods: The link to access the SAT question set was sent via email to 30 SIFO-EAHP-WG participants associated with 23 healthcare settings (14 hospitals – two private and 12 public; 8 Local Health Units; 1 university). All data obtained from the SAT was collected and analysed in an Excel file. Results: Twenty participants (67%) belonging to 61% of the healthcare services answered the survey: 10 hospitals (H) of which one private and nine public, and four Local Healthcare Units (ASL). The level of implementation was: S1 61.3% (H: 67.7% [95% CI : 59.6–75.9]; ASL: 45.4% [29.1–61.6]); S2: 72.6% (H: 80% [74.2–85.8]; ASL: 53.9% [26.1–81.8]); S3: 83.9% (H: 89% [83.5–94.5]; ASL: 71.3% [34.7–107.8]); S4: 52.6% (H: 61.1% [48.9–73.3]; ASL: 31.3% [18.6–44.0]); S5: 73.7% (H: 82.6% [74.1–91.1]; ASL: 51.4% [38.9–64.0]); S6: 70.8% (H: 76.7% [63.4–89.9]; ASL: 56% [38.7–73.3]), confirming the high variability mainly for S1 and S4. Conclusion: The results have shown how the level of implementation of the Statements in the analysed sample is high. However, the variability between the single Statements highlights the need to obtain a complete picture of the Italian setting. Such data is fundamental for SIFO-EAHP-WG to be able to define an effective action plan to support a harmonised implementation of the Statements in Italy. References and/or acknowledgements: A special thank you to SIFO and Piera Polidori for their encouragement and support.